Effect of rhodamine B degradation during the formation of lepidocrocite. Issue 1 (March 2015) - Chen, Rufen; Zhao, Jianrong; Liu, Hui; Wei, Yu
Graphical abstract: Highlights: Adsorption and degradation of RhB during lepidocrocite formation were analyzed. Adsorption and degradation of RhB were affected by the action of system itself. Comprehensive effect occurred in the degradation of RhB during the reaction. Abstract: This paper described the adsorption and degradation of rhodamine B (RhB) during lepidocrocite (γ-FeOOH) formation by air oxidation of Fe(OH)2 under visible-light irradiation in the presence of trace ethylenediaminetetracetic acid (EDTA). The results showed that RhB could be adsorbed on a green rust II (GR II) intermediate and on the γ-FeOOH product surface during γ-FeOOH formation and be degraded via heterogeneous and homogeneous photo-Fenton-like reactions. Fe 2+ and H2 O2 coexisted in the reaction system, and Fe 2+ or H2 O2 both promoted the adsorption and degradation of RhB. As the reaction proceeded, the increase in acidity enhanced the efficiency of the photo-Fenton-like reactions, which led to an increase in RhB degradation. The adsorbed RhB exhibited desorption behaviors because of the transformation of GR II and growth of γ-FeOOH. A possible mechanism was suggested for the comprehensive effect of RhB degradation during the reaction.